2017
DOI: 10.9734/jamps/2017/33831
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Antioxidant Activities of Dacryodes edulis Methanolic Leaf Extract

Abstract: This work was carried out in collaboration between both authors. Author OOO designed and carried out the study and performed the statistical analysis of the manuscript. Author APO carried out the study, managed the analyses of the study, managed the literature searches and wrote the first draft and the protocol. Both authors read and approved the final manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…These findings concur with those obtained by Aristimunha et al (2016) and Ogbe and Affiku (2012) . Proportionately, the amounts determined from different plant parts in this study (see Table 2 ) compare well with those reported in other studies evaluating D. edulis phytochemical composition ( Ogboru, 2015 ; Ebana et al, 2016 ; Okolo et al, 2016 ; Oyetunji and Opeyemi, 2017 ). These compounds have been noted to possess bactericidal, virucidal, fungicidal, and antiparasitical properties which can be exploited in pharmaceutical medicine or animal feed additives.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These findings concur with those obtained by Aristimunha et al (2016) and Ogbe and Affiku (2012) . Proportionately, the amounts determined from different plant parts in this study (see Table 2 ) compare well with those reported in other studies evaluating D. edulis phytochemical composition ( Ogboru, 2015 ; Ebana et al, 2016 ; Okolo et al, 2016 ; Oyetunji and Opeyemi, 2017 ). These compounds have been noted to possess bactericidal, virucidal, fungicidal, and antiparasitical properties which can be exploited in pharmaceutical medicine or animal feed additives.…”
Section: Discussionsupporting
confidence: 89%
“…The phytochemical analysis of the three D. edulis plant parts was determined qualitatively ( Nwokonkwo, 2014 ; Oyetunji and Opeyemi, 2017 ) and quantitatively ( Madhurima et al, 2014 ) using three replicate for each of the parts. While the proximate analysis was carried out for all experimental diets in which the dry Matter (DM) was determined by drying samples at 105 °C overnight.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported antibacterial activity of the ethyl acetate fraction of D. edulis leaves against Staphylococcus aureus , Klebsiella pneumoniae , and P. aeruginosa , with inhibition zones of 29, 28, and 25 mm, respectively [ 83 ]. Methanol extraction of D. edulis leaves also showed antibacterial activity against various bacteria, including Bacillus stearothermophilus , K. pneumoniae , Bacillus polymyxa , Citrobacter freundii , P. aeruginosa , Trueperella pyogenes , Enterococcus faecalis , Escherichia coli , Micrococcus luteus , Shigella sp., and S. aureus , with inhibition diameters ranging from 12.0–23.3 mm, compared to 13.0–31.0 and 18.3–29.3.5 mm for streptomycin and ampicillin, respectively [ 84 ]. The flavonoid content of D. edulis exhibited antimicrobial activity against Proteus mirabilis and Candida albicans with IC 50 values of 5 and 10 mg/mL, respectively [ 85 ].…”
Section: Bioactivity Studiesmentioning
confidence: 99%
“…Antibacterial effect of the essential oil as well as the organic extracts of D. edulis plant has been reported [8,3]. It was indicated that the leaf extract of Dacryodes edulis possess broad spectrum antibacterial activity in a recent study [9].…”
Section: Introductionmentioning
confidence: 99%